Rare bird documentation form for Glaucous Gull at Saylorville Reservoir in 1986 - Dinsmore, Stephen J.et al (1986)
Rare bird documentation form for one to four Glaucous Gulls at Saylorville Reservoir on November 22 to 24, 1986. Epson - sheet feed